2014
DOI: 10.1111/joa.12176
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of the chemo‐attractive receptor ChemR23 and occurrence of apoptosis in human chondrocytes isolated from fractured calcaneal osteochondral fragments

Abstract: To study the expression level of a panel of pro/anti-apoptotic factors and inflammation-related receptors in chondral fragments from patients undergoing surgical treatment for intra-articular calcaneal fractures, cartilage fragments were retrieved from calcaneal fractures of 20 patients subjected to surgical treatment. Primary cultures were performed using chondral fragments from fractured and control patients. Chondrocyte cultures from each patient of the fractured and control groups were subjected to immunof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…IL-1β can be secreted by chondrocytes, mononuclear cells, osteoblasts and synovial cells. Previous studies have reported that IL-1β may stimulate apoptosis of chondrocytes and tendon cells (22,23) by upregulating the expression of Bax and caspase-3 (24), and suppressing the expression of Bcl-2 and PARP (25). Several studies (21,26,27) have demonstrated that IL-1β promotes catabolic activity of chondrocytes through two major mechanisms: IL-1β suppresses the synthesis of major extracellular matrix proteins, such as aggrecan and COL2; and IL-1β stimulates the release of several proteolytic enzymes, including MMPs such as MMP1, MMP3 and MMP13.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β can be secreted by chondrocytes, mononuclear cells, osteoblasts and synovial cells. Previous studies have reported that IL-1β may stimulate apoptosis of chondrocytes and tendon cells (22,23) by upregulating the expression of Bax and caspase-3 (24), and suppressing the expression of Bcl-2 and PARP (25). Several studies (21,26,27) have demonstrated that IL-1β promotes catabolic activity of chondrocytes through two major mechanisms: IL-1β suppresses the synthesis of major extracellular matrix proteins, such as aggrecan and COL2; and IL-1β stimulates the release of several proteolytic enzymes, including MMPs such as MMP1, MMP3 and MMP13.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence analysis was carried out to assess the expression of MAP LC3 in bone biopsies and LC3 and Apaf‐1 in the cell cultures. MLO‐Y4 cells, cultured in different conditions in multiwell chamber slides, and bone biopsy samples were treated and observed as previously described . Samples were incubated with the following antibodies: rabbit anti‐MAP LC3 (Code n. sc‐134226), mouse anti‐Apaf‐1 (Code n. sc‐135836, Santa Cruz Biotechnology, Inc., Dallas, TX, USA); goat anti‐rabbit Cy3 (Code n. C2306) and sheep anti‐mouse FITC (Code n. F2883, Sigma‐Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…The confocal imaging was performed on a Leica TCS SP2 AOBS confocal laser scanning microscope (Leica S.p.A.). To quantify MAP LC3‐positive cells, 5 to 6 slides were examined at 40× magnification for each condition, in order to count almost 1000 cells as previously described . All results are expressed as the mean % ± SD.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations